Effects of partial defoliation on carbon and nitrogen partitioning and photosynthetic carbon uptake by two-year-old cork oak (Quercus suber) saplings (Tree Physiology, 2004)
At the end of the growing season in late July, 20-month-old cork oak (Quercus suber L.) saplings were partially defoliated (63% of leaf area) to evaluate their ability to recover leaf area after defoliation. At 18 and 127 days after defoliation, changes in starch and nitrogen pools were determined in leaves and perennial organs, and variations in photosynthetic carbon uptake were investigated. To determine the role of stored nitrogen in regrowth after defoliation, plant nitrogen was labeled in the previous winter by enriching the nutrient solution with 15N. Plants recovered the lost leaf area in 127 days. Although there was remobilization of starch and nitrogen from leaves and perennial organs, the availability of resources for growth in the following spring was not decreased by defoliation. On the contrary, starch concentration in coarse roots was higher in defoliated saplings than in control saplings, presumably as a result of the higher net CO2 exchange rate in newly developed leaves compared with pre-existing leaves.
10.1093/treephys/24.1.83

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.

Diurnal changes in photoprotective mechanisms in leaves of cork oak (Quercus suber) during summer (Tree Physiology, 1996)
Daily variations in photoprotective mechanisms were studied in sun and shade leaves of 40-year-old cork oak (Quercus suber L.) trees during early summer in Portugal. Although trees were not severely water stressed because predawn leaf water potentials remained high, photosynthesis and stomatal conductance decreased at midday. The midday depression in gas exchange was not reversed by short-term exposure to “optimal” conditions of temperature, light and vapor pressure deficit. Chlorophyll a fluorescence, maximum photochemical yield of photosystem II and the quantum yield of noncyclic electron transport showed midday depressions, but recovered by the evening. Both short-term changes in the components of the xanthophyll cycle (reversible de-epoxidation of violaxanthin during the day) as well as long-term changes (higher xanthophyll content in sun compared with shade leaves) were detected and may play a role in the dissipation of excess energy at midday. Because the activities of enzymes of the antioxidant system, superoxide dismutase and ascorbate peroxidase, were high enough to cope with the increase in oxygen reactive species likely to arise under the stressful conditions of midday, we conclude that these enzymes may provide an additional mechanism for energy dissipation.
10.1093/treephys/16.1-2.115

Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)